Nitrogen and phosphorus constrain the CO2 fertilization of global plant biomas - Terrer,C; Prentice,I; Jackson,R; Keenan,T; Kaiser,C; Vicca,S; Fisher,J; Reich,P; Stocker,B; Hungate,B; Penuelos,J; McCallum,I; et al. (Nature Climate Change, 2019)
Elevated CO2 (eCO2) experiments provide critical information to quantify the effects of rising CO2 on vegetation. Many eCO2 experiments suggest that nutrient limitations modulate the local magnitude of the eCO2 effect on plant biomass, but the global extent of these limitations has not been empirically quantified, complicating projections of the capacity of plants to take up CO2. Here, we present the first data-driven global quantification of the eCO2 effect on biomass based on 138 eCO2 experiments. The strength of CO2 fertilization is primarily driven by nitrogen (N) in ~65% of global vegetation, and by phosphorus (P) in ~25% of global vegetation, with N- or P-limitation modulated by mycorrhizal association. Our approach suggests that CO2 levels expected by 2100 can potentially enhance plant biomass by 12±3% above current values, equivalent to 59±13 PgC. The global-scale response to eCO2 we derive from experiments is similar to past changes in greenness9 and biomass10 with rising CO2, suggesting that CO2 will continue to stimulate plant biomass in the future despite the constraining effect of soil nutrients. Our research reconciles conflicting evidence on CO2 fertilization across scales and provides an empirical estimate of the biomass sensitivity to eCO2 that may help to constrain climate projections.